Multifunctional properties of PBAT with hemp (Cannabis sativa) micronised fibres for food packaging: cast films and coated paper - Lamsaf, Hafsae (2023)
Hemp (Cannabis sativa) stalk fibres from industry residues were incorporated into polybutylene adipate terephthalate, a synthetic biodegradable polyester, to produce films and paper coatings. The lignocellulosic components and the chemical composition of the fibres were analysed, and the results highlight the bioactivity due to cannabinoids, alkanoids, and lignin, among others, making the fibres attractive for active food packaging. The incorporation, without chemical modification, of 2% (w/w) hemp in the PBAT matrix increased the water vapour permeability of PBAT around 22%. The impact on mechanical properties was determined, and the results show that the PBAT/hemp film is less stretchable but stronger than the pure PBAT film. The incorporation of hemp enhanced significantly the compostability of PBAT. The PBAT/hemp films and paper coatings composted two times faster than those using pure PBAT.